Edukasi Pijat Bayi dengan Metode Demonstrasi dan Simulasi Melalui Media Video di Kota Jambi - Armina Armina; Nurfitriani Nurfitriani (3031-8572, 2025)
Baby massage is a gentle massage that is important for the growth and development of babies. Baby growth and development can be helped by baby massage. Posyandu Teratai V Legok has never been given baby massage education and has been educated at the Putri Ayu Health Center in Jambi City. The purpose of this community service is to provide education about baby massage using video media. The implementation of this Community Service was carried out on May 8, 2024, at Posyandu Teratai V in the working area of ​​the Putri Ayu Health Center in Jambi City, targeting 10 mothers using the video method and baby massage simulation. The implementation stage carried out a pre-test session, education, playing videos, baby massage simulations, and the evaluation stage in the form of a post-test session for skills in doing baby massage. The results of this Community Service were that mothers were enthusiastic about participating in baby massage video education and the knowledge gained after education increased to an average score of 13 out of 7.9 and baby massage skills to an average score of 28.6 out of 4.1. The results of this Community Service can be continued at other integrated health posts by training integrated health post cadres or health center officers.